2019
DOI: 10.1177/0825859719851492
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Support Service, Emergency Department, and Hospital Utilization in Patients with Advanced Cancer: A Descriptive Study

Abstract: Context: Palliative care in oncology provides multiple benefits, however access to specialty palliative clinicians is limited in community cancer centers. Individual support services are more often available, but little is known on the utilization and impact of these services. Objectives: To describe the utilization of outpatient support services in the advanced cancer population and the association with ED and hospital use in a community setting. Methods: A retrospective chart review of 314 patients with adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…One notable aspect of the results is that those with a palliative treatment strategy and those with no tumour-directed treatment used more acute health care than did patients with a curative treatment strategy (Table 4 ). This is in line with results from previous studies that identified high use of unplanned health care among patients with incurable cancer [ 17 , 18 , 34 ]. Studies by Craigs et al (2018) and Grande et al (2002) showed that regular contact with an oncology specialist was associated with increased access to both community and hospital-based palliative care and referral to palliative home care [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…One notable aspect of the results is that those with a palliative treatment strategy and those with no tumour-directed treatment used more acute health care than did patients with a curative treatment strategy (Table 4 ). This is in line with results from previous studies that identified high use of unplanned health care among patients with incurable cancer [ 17 , 18 , 34 ]. Studies by Craigs et al (2018) and Grande et al (2002) showed that regular contact with an oncology specialist was associated with increased access to both community and hospital-based palliative care and referral to palliative home care [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to the ASCO, high care quality is characterized by low frequency of ED visits and hospitalizations and high rate of hospice enrolment [ 16 ]. Despite the recognized need for proactivity, studies indicate that acute health care is common among patients with advanced cancer [ 17 , 18 ]. A cross-national study on patients dying from cancer in seven developed countries reports that 44–64% were admitted to acute care hospitals and 28–58% visited the ED in the final month of life [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare chaplaincy is considered a ‘support service’ 56 (p. 34) and a component of Mertens et al’s 1 (p. 3681) description of a ‘fluid’ team of ‘collaborating professionals’ which, given the increasingly complexity of illness, is likely to be a more widespread approach for the future. In this fluidic environment, enabling professionals to work together in the pursuit of high-quality care can prove challenging.…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…Patients with advanced cancer have been shown to utilize the and inpatient healthcare services, even despite high utilization of other outpatient support services [ 35 ]. According to a recent study in the US, patients with advanced cancer presented to the ED despite recommendations for early provision of palliative care, from which 6.5 % of the patients had received palliative and 1.3 % prior hospice care [ 36 ].…”
Section: Discussionmentioning
confidence: 99%